The study of backgrounds and the incoherent contribution for neutrino trident production - Becerra Aguilar, José Antonio (Pontificia Universidad Católica del Perú, 2018)
We studied dimuon events arising from trident production, for both coherent and incoherent processes, as well as relevant backgrounds, in order to predict the number of expected events observed in the lifetimes of current and forthcoming neutrino experiments. In particular, for this thesis, we focused in building the implementation of the incoherent contribution within the context of the GENIE montecarlo generator. We also developed relatively detailed GEANT4 geometries for the MINERvA detector as well as the DUNE Near Detector, for the Liquid Argon (LArTPC) and Straw Tube Tracker (STT) proposals. A very careful study of the backgrounds for the incoherent case was carried, in order to complement the study already done for the coherent contribution. Then, we combined the signals for the coherent and incoherent processes to realize a more realistic study of the expected number of events. The ROOT TMVA package for multivariate analysis was then used to filter signal from background. The results are presented in terms of number of events, and are calibrated based on the detector exposure in the lifetime of the MINERvA detector and DUNE Near Detector.
Keywords: Neutrinos; Física de altas energías; https://purl.org/pe-repo/ocde/ford#1.03.00